The impact of social media on knowledge, attitude and practices (KAP) towards sustainable consumption in higher education institutions - Hammna Jillani; Muhammad Nawaz Chaudhry; Syeda Rabab Jafri; Hesan Zahid (Cleaner and Responsible Consumption)
Purpose: Overconsumption is an escalating problem, the unchecked levels of production and consumption craft a vicious cycle that results in excessive exploitation of natural resources. This research attempts to assess the sustainable consumption practices (SDG 12) of university students by implying Knowledge, Attitude, and Practices (KAP) Framework and explores the role of social media in disseminating environment related information and content. Design/methodology/approach: Drawing on a sample of (n = 485) university students from various public and private sectors, this quantitative research used a survey designed to test the KAP framework, analyzed using Structural Equation Modeling via SmartPLS 4.0. Findings: The study reveals that only knowledge alone may not significantly influence the sustainable consumption practices of university students rather the external factors like social media usage can significantly influence the relationship between knowledge and sustainable consumption practices. However, knowledge is found to have a positive impact on the attitude (towards sustainable consumption) which can further lead to positive practices by the students. The mediating role of social media integrated with the moderating role of gender in using social media platforms has been observed in the study. Originality: The novelty of this work lies in identifying the mediating role of social media usage as an agent to promote sustainable consumption practices. Young adults can be made mindful of their consumption and purchasing habits by making them realize the harsh reality of overconsumption. Collaborative efforts by the education sector along with environmental campaigns and content of social media platforms can result in augmented awareness thus, raising the idea of sustainable consumption among students and helping them to make the right adoptions for safeguarding natural resources.